Laughter Therapy terhadap Tingkat Kecemasan Pasien Hemodialisis - Toding, Dewiyanti; Ariyanti, Isnah; Bakri, Nirmala; Mahmud, Reflin; Khotimah, Husnul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The objective of this study is to evaluate the efficacy of laughter therapy in reducing anxiety levels among individuals undergoing hemodialysis. This study employs a quasi-experimental design with a quantitative approach, utilizing a non-equivalent group design comprising an intervention group that receives laughter therapy and a control group that receives regular education from hemodialysis nurses. The results demonstrated that following a four-week intervention period, there was a notable reduction in anxiety levels among the intervention group, with a p-value of 0.04. However, the laughter therapy intervention group exhibited a more pronounced decline in anxiety levels, with a p-value of 0.00. In conclusion, it can be recommended that laughter therapy interventions be applied in the implementation of nursing care in the hemodialysis unit to reduce anxiety levels, thereby improving the quality of life of hemodialysis patients. Keywords: Anxiety, Hemodialysis, Laughter therapy